INNOVATION OF DIGITAL SERVICES FOR THE SUNGAI PETAI VILLAGE GOVERNMENT, KAMPAR KIRI HILIR DISTRICT, KAMPAR REGENCY - Maharani Maharani; Adianto Adianto (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
Digital-based village government service innovation. Effective and efficient service is a demand from the community to government agencies in providing services. The Sungai Petai Village Government is one of the village governments that innovates the first digital application-based service in Riau. The innovation in question is the Halaman Kampung application. The purpose of creating this Halaman Kampung application is to provide more effective and efficient services to village communities. The purpose of this study is to describe the Innovation of Village Government Services Based on Digital Applications in Sungai Petai Village, Kampar Kiri Hilir District, Kampar Regency. This study uses the innovation theory by Bugge et al. 2018, in which there are six indicators, namely: governance and innovation, sources of the ideas for innovation, innovation culture (innovation culture). ), capabilities and tools (abilities and tools), objectivies, outcomes, expenses and obstacles (goals, results, costs, and obstacles), collecting innovation data for single innovation (collecting innovation data for single innovations). This type of research is a descriptive research with a qualitative approach. Data collection was done by using the methods of observation, interviews, and documentation of both primary and secondary data. The results of this study indicate that: 1) the innovation of the home page application has been going well because the community has used the home village application in various types of administrative services. 2) the supporting factors in the success of hometown innovation are the fulfillment of service innovation digitization facilities, adequate digital applications, sufficient understanding of innovation.